Pengaruh Kompetensi Karyawan Dan Penerapan Sistem Informasi Manajemen Rumah Sakit Terhadap Kinerja Karyawan - Arief Mardhiko; Yuni Pratikno; Sri Wahyuningsih (Journal of Innovative and Creativity, 2025)
To determine and analyze the partial effect of Employee Competence on Employee Performance at Sari Asih Ciputat Hospital. To determine and analyze the partial effect of Hospital Management Information System on Employee Performance at Sari Asih Ciputat Hospital. To determine and analyze the simultaneous effect of Employee Competence and Hospital Management Information System on Employee Performance at Sari Asih Ciputat Hospital. From this understanding, the population in this study is 524 Patients of Sari Asih Ciputat Hospital. using the Slovin technique With this technique, a sample of 84 patients was taken at Sari Asih Ciputat Hospital. Based on the coefficients table above, the t-count value for the Employee Competence variable (X1) is 4.624 while the t-table value for N = 84 is 1.988. So 4.624> 1.988, then H0 is rejected and Ha is accepted, it can be stated that Employee Competence (X1) has a significant effect on Employee Performance (Y). Based on the coefficients table above, the t-count value for the Hospital Management Information System Implementation variable (X2) is 4.961, while the t-table value for N = 84 is 1.988. So 4.961> 1.988, then H0 is rejected and Ha is accepted, it can be concluded that partially the Hospital Management Information System Implementation variable (X2) has an effect on Employee Performance (Y). The ANOVA test value obtained an F-count value of 263.022, while F-table (◻ 0.05) for N = 84 was 2.71. So Fcount > from Ftable (◻ 0.05) or 263.022 > 2.71 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Employee Competence (X1) and Implementation of Hospital Management Information System (X2) together have a positive effect on Employee Performance (Y). The Adjusted R Square (R2) value is 0.867. This shows that 86.7% of Employee Competence (X1) and Implementation of Hospital Management Information System (X2) simultaneously affect Employee Performance (Y) while the remaining 13.3% is influenced by other factors not examined in this study.